ALCOHOL ABUSE AND COGNITIVE COMPLAINTS AFTER MILD TRAUMATIC BRAIN INJURY IN OLDER ADULTS. (11th November 2018) - Tran, V; Garcia, J; Radmanesh, D; Vitale, G; Stripling, A
Abstract: Traumatic brain injuries significantly impact older adults; accounting upwards of 80, 000 emergency room visits a year and resulting in an estimated annual cost of $2.2 billion. Mild traumatic brain injury (mTBI), which is associated with concentration, memory, and decision-making difficulties, is often experienced more frequently than severe TBI in older adults yet remains an underexplored area. Additionally, despite noted age related declines in alcohol processing and harmful interactions between alcohol and medication, alcohol use remains a common concussion coping strategy. Despite the gravity and impact of this public health issue, there remains a paucity of research exploring the effects of alcohol abuse as a common mTBI coping strategy on cognitive symptoms. Thus, the current study seeks to explore this link. Researchers utilized 3, 458 older adult participants from the de-identified National Alzheimer's Coordinating Center (NACC) database to explore differences in alcohol abuse and cognitive profiles between participants with recent (active) mTBI, remote (inactive) mTBI, and no history of TBI through a multivariate analysis of variance (MANOVA). Results revealed a significant overall effect for the model at α=.05, F(34, 6880), p < .001, Wilk's Λ = .971 and additional investigation showed, relative to those without a history of TBI, those with a remote history of mTBI were more likely to exhibit alcohol abuse, and there were no significant differences in the cognitive profiles of the two groups. Implications of the current presentation include highlighting the importance of psycho-education regarding alcohol's deleterious influence on cognition, particularly within the older mTBI population.